Mentoring leaders : wisdom for developing character, calling, and competency - Pue, Carson (Grand Rapids, Mich. : Baker Books, 2005)
Who are tomorrow's Christian leaders? Christian churches and organizations will fill fifty thousand strategic ministry positions within the next five to ten years. But what will be required of these leaders, and who will prepare them? If you are a new leader or find yourself with the unique opportunity to mentor an emerging leader, you know the high expectations and changing demands of ministry positions. In Mentoring Leaders Carson Pue offers trustworthy, substantial guidance to prepare you for service. He boldly addresses the spiritual aspects of Christian leadership development to help you strengthen your character, calling, and competency. With an accessible offering of insight and encouragement, Pue will help you sharpen your vision, shape your values, and share your leadership adventures. --
The process of mentoring : the history and background -- Starting with new awareness : the foundational beginning of leadership development -- Freeing up : the unchaining of God's leaders -- Visioneering -- Practical vision helps -- Implementing the vision -- Stepping out vision -- Budgeting time and resources -- Measuring people and outcomes -- Sustaining in leadership -- Fear, loneliness, and other challenges -- Accountability.
Includes bibliographical references (pages 263-266).
Keywords: Christian leadership; Mentoring in church work; Leadership -- Religious aspects -- Christianity